Converting Bridge Voltages to Load Impedance: Method 2
There is an alternative way of doing Step 2 as described in Converting Bridge Voltages to Load Impedance: Method 1
The RHS of Eq4 with $Z_l = R+jX$ is
$$\vert \frac{R-50+jX}{R+50+jX}\vert $$ |
Squaring the modulus $\vert a+jb\vert $ gives $a^2+b^2$, so squaring top and bottom of the equation above gives
Eq6 | $$\frac{(R-50)^2+X^2}{(R+50)^2+X^2}=\frac{R^2-100R+2500+X^2}{R^2+100R+2500+X^2}$$ |
But $R^2+X^2 = \vert Z_l\vert ^2$ so
Eq7 | $$\frac{(R-50)^2+X^2}{(R+50)^2+X^2}=\frac{\vert Z_l\vert ^2-100R+2500}{\vert Z_l\vert ^2+100R+2500}$$ |
Which can be solved to give
$$R = \frac{\vert Z_l\vert ^2+50^2}{100}\frac{1-(\frac{V_r}{V_f})^2}{1+(\frac{V_r}{V_f})^2}$$ |
Now that we know $R$ as well as $\vert Z_l\vert $, we can use $ X=\sqrt{\vert Z_l\vert ^2-R^2} $ to get the complex impedance and VSWR.
We can rewrite these equations to use the bridge voltages directly:
$$R = \frac{(50\frac{V_z}{V_a})^2+50^2}{100} \frac{1-(\frac{V_r}{V_f})^2}{1+(\frac{V_r}{V_f})^2}$$ |
$$X = \pm\sqrt{(50\frac{V_z}{V_a})^2 - R^2}$$ |